s-Tetrazine: Robust and Green Photoorganocatalyst for Aerobic Oxidation of N,N-Disubstituted Hydroxylamines to Nitrones - Lyu, Jiyuan; Le, Tuan; Claraz, Aurélie; Allain, Clémence; Audebert, Pierre; Masson, Géraldine (Synlett, 2021)
Efficient photocatalytic aerobic oxidative dehydrogenation reactions of N,N-disubstituted hydroxylamines to nitrones were developed with an in situ generated photocatalyst based on commercially available 3,6-dichlorotetrazine. This process affords a wide range of nitrones in high yields under mild conditions. In addition, an oxidative (3+3) cycloaddition between an oxyallyl cation precursor and a hydroxylamine was also developed.
Keywords: s-tetrazine; photoorganocatalyst; nitrones; sequential oxidative (3+3) cycloaddition